PERANCANGAN SISTEM CUCI TANGAN DENGAN NOTIFIKASI PERSEDIAAN AIR SECARA OTOMATIS MENGGUNAKAN MIKROKONTROLLER ATMEGA328 - Nirwan Sinuhaji; Asprina Br. Surbakti; Muhammad Ainur Rafiq (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2022)
Maintaining cleanliness is very important during a pandemic because maintaining cleanliness is an effort to minimize the spread of the COVID-19 virus during a pandemic. One of them is to maintain cleanliness by washing hands. Activities in meeting daily needs are unavoidable, such as activities outside the home, crowded places and shopping at stores directly, which makes people a gathering place in one place. This can cause the spread of the virus. Covid-19 is an infectious disease caused by a type of corona virus. The activity of washing hands is something that is usually done by humans, but it has benefits and effects that are quite significant for the health of the body. Usually, hand washing is done manually by opening the faucet head or from a tub filled with water and then taking it with a dipper from one's own hand. Usually, after washing their hands, people need a means to dry their hands. But at this time manually drying hands can increase the spread of viruses or bacteria. With the design of an automatic hand washer and dryer to be more efficient in breaking the chain of the spread of Covid 19. This machine is also equipped with a body temperature checking system to determine the health of the people who are washing their hands. This tool works automatically so that our hands will be more guaranteed clean because the user does not need to touch the faucet or soap lever to operate it. The automatic water flow speed makes it easier for users to operate so that it can save water flow and be more efficient or not waste water. Water supplies in water reservoirs can also make it difficult for officers to find out how much water is available in water reservoirs, causing officers to spend a lot of time checking water supplies, this can be overcome by notification of water supplies on smartphones using the Telegram application that can fill water automatically. One of the efforts to avoid water wastage is to design a hand washing place with a water output discharge based on the distance of the user's hand and also based on the amount of soap automatically so that it can be used easily and practically.